Spaces apart: public parks and the differentiation of space in Leeds, 1850–1914. (August 2021) - Booth, Nathan; Churchill, David; Barker, Anna; Crawford, Adam
Abstract: While the Victorian ideal of the public park is well understood, we know less of how local governors sought to realize this ideal in practice. This article is concerned with park-making as a process – contingent, unstable, open – rather than with parks as outcomes – determined, settled, closed. It details how local governors bounded, designed and regulated park spaces to differentiate them as 'spaces apart' within the city, and how this programme of spatial governance was obstructed, frustrated and diverted by political, environmental and social forces. The article also uses this historical analysis to provide a new perspective on the future prospects of urban parks today.